Using alumina and zirconia ceramic composite in dogs: A biocompatibility study - Korakot Nganvongpanit (2018)
This research was to study the biocompatibility of in-house ceramic materials; consisted of different ratios of magnesium-doped alumina (MDA) and yttria-stabilized zirconia (YSZ). Materials 1-3 (M1-3) were 40, 50 and 60% MDA, respectively. Six male dogs were used for subcutaneous implants in the right hind limb for a 12-week period. Blood was collected from dogs weekly to evaluate health. Tissue surrounding material was then collected for histological evaluation and real-time PCR. Five transcripts, including TNF-α, IL-6, IL-13, IFN-g and MMP-9, were quantified using real-time PCR. The hardness of all materials was tested prior to and after implantation. The results found that all of the biopsy specimens showed neither foreign body reaction nor granulation tissue formation. Compared to the control, expression of MMP-9 in M1 was found to be significantly down-regulated (P < 0.05); expression of TNF-α, IL-13 and MMP-9 in M2 was found to be significantly different (P < 0.05); and in M3, IL-13 was found to be significantly up-regulated (P < 0.05). Hardness in M1 was significantly decreased (P < 0.05) after 12 weeks of implantation. In conclusion, M3, which consisted of 60% MDA, is a candidate material for use as a bone substitute in dogs.